Work-Life Balance and Time Flexibility of Female Employees in the Home Industry: A Systematic Literature Review - Telly Pauline Ulviana Siwi; Debi Septiani; Yike Diana Putri; Agung Indriansyah (Journal of Creative Power and Ambition (JCPA), 2026)
Home-based food industries, such as the traditional "kentang mustofa" processing business, represent a labor-intensive micro-enterprise subsector predominantly staffed by women who bear a dual role as production workers and household managers. This condition creates the potential for role conflict that may reduce work focus and productivity. This study aims to map research trends, synthesize the literature consensus on the effect of Work-Life Balance (WLB) on productivity, and examine how time flexibility affects the daily productivity of women workers in the informal sector, using a Systematic Literature Review (SLR) guided by the PRISMA 2020 framework. Searches across Google Scholar, Garuda, DOAJ, ScienceDirect, Scopus, and Emerald yielded 20 eligible articles from 346 initial records. The synthesis indicates that WLB is consistently and positively associated with employee productivity and performance, although the strength of this relationship is moderated by sector, gender, and job hierarchy. Time flexibility helps informal-sector women reduce role conflict and maintain production stability, yet unstructured flexibility risks lowering output in daily-target-based industries. The study recommends an adaptive time-management model based on task rotation and flexible work blocks for food-based micro-enterprises as a strategy to balance productivity and the well-being of women workers